VD_FINDINFO Jug / 2019 / 245 vom 15. November 2017 - VD Tribunal cantonal (2017)
DÉCISION DE RENVOI, PEINE COMPLÉMENTAIRE, CONTRAINTE SEXUELLE, TENTATIVEDROIT PÉNAL | 189 al. 1 CP, 22 al. 1 CP, 49 al. 1 CP